Moral Intelligence -Theory and in Education - Monika Dacka (The Francis de Sales Scientific Society (TNFS.PL), 2024)
Morality and intelligence influence various aspects of human life and action. They contribute to a certain stabilisation of a young person's functioning in a given society. The development and technological progress that is taking place is conducive to the development of young people, the satisfaction of certain needs, but it cannot guarantee the possibility of shaping basic values such as freedom, justice or responsibility. Currently, material and individualistic values are increasingly promoted. References to moral ideals based on truth, honesty and love, on the other hand, are less frequent. These are important when making future choices or decisions. A particularly important task today, in the face of various threats, addictions and value crises, is to shape the moral intelligence of young people. It involves having strong ethical and moral convictions and acting in accordance with them. The purpose of this article is to introduce the concept of moral intelligence, to provide a definition and a conception of the research issue under consideration on a psychological level. It also shows some conditions of its formation during childhood and adolescence.  The considerations undertaken in the article show the importance of moral intelligence in developing appropriate social attitudes, behaviour, acquiring moral principles, teaching responsibility, sensitivity to the suffering of others in adolescents.